2008
DOI: 10.1111/j.1365-313x.2008.03617.x
|View full text |Cite
|
Sign up to set email alerts
|

Stress generation in the tension wood of poplar is based on the lateral swelling power of the G‐layer

Abstract: SummaryThe mechanism of active stress generation in tension wood is still not fully understood. To characterize the functional interdependency between the G-layer and the secondary cell wall, nanostructural characterization and mechanical tests were performed on native tension wood tissues of poplar (Populus nigra  Populus deltoids) and on tissues in which the G-layer was removed by an enzymatic treatment. In addition to the wellknown axial orientation of the cellulose fibrils in the G-layer, it was shown tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
83
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 96 publications
(94 citation statements)
references
References 26 publications
9
83
2
Order By: Relevance
“…www.plantphysiol.org/cgi/doi/10.1104/pp.109.149542 1994Yamamoto, 1998Yamamoto, , 2004Alméras et al, 2005Alméras et al, , 2006Bowling and Vaughn, 2008;Goswami et al, 2008;. The specific organization of the G-layer suggests a tensile force induced in the microfibrils during the maturation process.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…www.plantphysiol.org/cgi/doi/10.1104/pp.109.149542 1994Yamamoto, 1998Yamamoto, , 2004Alméras et al, 2005Alméras et al, , 2006Bowling and Vaughn, 2008;Goswami et al, 2008;. The specific organization of the G-layer suggests a tensile force induced in the microfibrils during the maturation process.…”
mentioning
confidence: 99%
“…Different hypotheses have been proposed to explain this mechanism, such as the contraction of amorphous zones within the cellulose microfibrils (Yamamoto, 2004), the action of xyloglucans during the formation of microfibril aggregates (Nishikubo et al, 2007;, and the effect of changes in moisture content stimulated by pectin-like substances (Bowling and Vaughn, 2008). A recent work (Goswami et al, 2008) argued an alternative model, initially proposed by Mü nch (1938), which proposed that the maturation stress originates in the swelling of the G-layer during cell maturation and is transmitted to the adjacent secondary layers, where the larger MFAs allow an efficient conversion of lateral stress into axial tensile stress. Although the proposed mechanism is not consistent with the known hygroscopic behavior of tension wood, which shrinks when it dries and not when it takes up water (Clair and Thibaut, 2001;Fang et al, 2007;Clair et al, 2008), this hypothesis focused attention on the possible role of cell wall layers other than the G-layer.…”
mentioning
confidence: 99%
“…A possible explanation has been proposed in a recent study whereby the contraction of the fibre is not caused by the G-layer directly, but by an interaction of the G-layer with the surrounding secondary cell wall (Goswami et al 2008), a mechanism that had been first suggested by Münch (1938).…”
Section: (B ) Movements Of Stem and Branchesmentioning
confidence: 97%
“…Apart from minor amounts of hemicelluloses and lignin (Joseleau et al 2004;Lehringer et al 2008), it consists of almost pure cellulose organized in aggregates of 30-40 nm diameter strictly parallel to the cell axis (MFA approx. 08) and can fill the whole lumen (Daniel et al 2006;Müller et al 2006;Goswami et al 2008). The G-layer is believed to be the operative part of the tension wood fibre (Côte & Day 1965;Clair et al 2003Clair et al , 2006 although the underlying mechanisms of stress generation are still discussed (Mellerowicz et al 2008) and high tensile stresses can be generated also in its absence (Qiu et al 2008).…”
Section: (B ) Movements Of Stem and Branchesmentioning
confidence: 99%
See 1 more Smart Citation